Long-term survival following medical management of Aspergillus endocarditis with dissemination as a consequence of steroid therapy in severe COVID-19 pneumonia - Kiran G. Kulirankal; Ann Mary; Merlin Moni; Gopal S. Pillai; Dipu T. Sathyapalan (Medical Mycology Case Reports, 2024)
A male in his 40's with no known comorbidities developed severe COVID-19 pneumonia and received a four-week course of methylprednisolone. The patient subsequently developed disseminated Aspergillus endocarditis, manifesting as multiple organ involvement including the heart, eyes, and brain. Despite the poor prognosis generally associated with fungal endocarditis, the patient survived following aggressive medical management with a combination of liposomal amphotericin b and voriconazole therapy and is now doing well for over two years and is off antifungal therapy for a year.